2012
DOI: 10.1089/jpm.2012.0014
|View full text |Cite
|
Sign up to set email alerts
|

A Nurse Practitioner Directed Intervention Improves the Quality of Life of Patients with Metastatic Cancer: Results of a Randomized Pilot Study

Abstract: An ARNP-directed intervention that explains the benefits of hospice and addresses advanced directives early in the course of metastatic cancer patients' treatment, is well received by the patients and their relatives and leads to measurable improvement in the patient's emotional and mental QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(129 citation statements)
references
References 14 publications
2
119
0
8
Order By: Relevance
“…Research has shown that advance care planning for end of life decisions can have a marked effect on lowering distress in palliative populations (42). Professional psychosocial support may facilitate family communication with healthcare teams and promote psychological adaptation (43).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that advance care planning for end of life decisions can have a marked effect on lowering distress in palliative populations (42). Professional psychosocial support may facilitate family communication with healthcare teams and promote psychological adaptation (43).…”
Section: Discussionmentioning
confidence: 99%
“…(Table 4) 31, 32 and the complete scoping review results are based on 269 NPs (93 from the ASTRO radiation oncology workforce survey), representing only 0.1% of the NPs in the United States. The small number of NPs represented in the research coupled with the significant projected increase in specialty NP care by the Center for Health Workforce Analysis illustrates the gap in knowledge of NP practice in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…The cancer survivor experiences different magnitudes of symptoms at different stages of the disease, with negative effects on quality of life, functional status and self-care. The end of life is reported as a period of increased incidence, intensity of symptoms and emotional distress [4]. Spichiger et al [5] reported that people admitted at palliative care units experienced 7 to 13 different symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' level of expertise showed to be a predictive indicator of increased health gains. Dyar et al [4] emphasize that the implementation of palliative care at an early stage promotes individual satisfaction. Education for self-management and follow-up were found to be positively associated with a higher quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation